Morphine in ventilated neonates: its effects on arterial blood pressure. Issue 1 (30th August 2005) - Simons, S H P; Roofthooft, D W E; van Dijk, M; van Lingen, R A; Duivenvoorden, H J; van den Anker, J N; Tibboel, D
Abstract : Objective: To study the effects of continuous morphine infusion on arterial blood pressure in ventilated neonates. Design: Blinded randomised placebo controlled trial. Setting: Level III neonatal intensive care unit in two centres. Patients: A total of 144 ventilated neonates. Inclusion criteria were postnatal age <3 days, ventilation <8 hours, and indwelling arterial line. Exclusion criteria were severe asphyxia, severe intraventricular haemorrhage, major congenital anomalies, neuromuscular blockers. Intervention: Arterial blood pressure was measured before the start and during the first 48 hours of masked infusion of drug (morphine/placebo; 100 μg/kg + 10 μg/kg/h). Outcome measures: Arterial blood pressure and blood pressure variability. Results: There were no significant differences in overall mean arterial blood pressure between the morphine group (median (interquartile range) 36 mm Hg (6) and the placebo group (38 mm Hg (6)) (p = 0.11). Although significantly more morphine treated patients (70%) showed hypotension than the placebo group (47%) (p = 0.004), the use of volume expanders and vasopressor drugs was not significantly different (morphine group, 44%; placebo group, 48%; p = 0.87), indicating the limited clinical significance of this side effect. Blood pressure variability was not influenced by routine morphine analgesia (p = 0.81) or additional morphine (p = 0.80). Patients with and without intraventricular haemorrhage showed no differences in blood pressure (Mann-Whitney U test 1953; p = 0.14) or incidence of hypotension (χ 2 test 1.16; df 1; p = 0.28). Conclusions: Overall arterial blood pressure, use of inotropes, and blood pressure variability were not influenced by morphine infusion. Therefore the clinical impact of hypotension as a side effect of low dose morphine treatment in neonates is negligible.